1996
DOI: 10.1152/jappl.1996.81.4.1807
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of nitric oxide and prostaglandins to reactive hyperemia in the human forearm

Abstract: We investigated the separate and combined contributions of nitric oxide (NO) and vasodilating prostaglandins as mediators of reactive hyperemia in the human forearm. Forearm blood flow (FBF) was measured with venous occlusion plethysmography after 5 min of ischemia. In one protocol (n = 12), measurements were made before and after intra-arterial administration of the NO synthase inhibitor NG-monomethyl-L-arginine (L-NMMA) to one forearm. In a separate protocol (n = 7), measurements were made before and after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
232
4
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 229 publications
(258 citation statements)
references
References 24 publications
18
232
4
4
Order By: Relevance
“…Regardless of the initiating event, the relaxation of vascular smooth muscle in the resistance vessels appears to be due in part to activation of inwardly rectifying potassium channels (K IR ) (9). The results of most (8,11,27,32) but not all (10, 23) studies have found that endothelium signaling pathways make little or no contribution to peak reactive hyperemia in humans. In isolated vessels, endothelium removal or inhibition of nitric oxide synthase partially blocked both peak reactive dilation and the duration of dilation (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the initiating event, the relaxation of vascular smooth muscle in the resistance vessels appears to be due in part to activation of inwardly rectifying potassium channels (K IR ) (9). The results of most (8,11,27,32) but not all (10, 23) studies have found that endothelium signaling pathways make little or no contribution to peak reactive hyperemia in humans. In isolated vessels, endothelium removal or inhibition of nitric oxide synthase partially blocked both peak reactive dilation and the duration of dilation (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, it seems reasonable to conclude that PGs do not play an essential role in skeletal muscle vasodilation during dynamic exercise under normoxic conditions. However, available evidence in humans suggests that PGs contribute to the rise in skeletal muscle blood flow following periods of limb ischemia (2,10,14,20). Moreover, COX inhibition has been shown to attenuate muscle vasodilation evoked by systemic hypoxia in rats (25).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are based on little to no change in muscle blood flow following PG synthesis inhibition. However, PGs have been reported to be involved in the regulation of skeletal muscle blood flow following periods of ischemia (2,10,14,20) and during systemic hypoxia (25). Therefore, it is possible that the PGs may become a more important vasodilator signal during exercise under conditions of reduced oxygen availability.…”
mentioning
confidence: 99%
“…In humans, moreover, insulin has been shown to stimulate vasodilatory effects by inducing endothelial nitric oxide (NO) production [21]. The idea that NO plays a part in intramuscular reactive hyperaemia is supported by most [22,23,24], but not all studies [25] using venous occlusion plethysmography. Therefore, in the present study, enhanced endothelial NO production might have contributed to insulin-mediated changes in intramuscular reactive hyperaemia.…”
Section: Discussionmentioning
confidence: 99%